Small bowel edema and lymphocytic duodenitis as severe reversible gastrointestinal toxicity of selpercatinib in RET fusion–positive non–small cell lung cancer: a case report - Scattolin, Daniela; Scagliori, Elena; Scapinello, Antonio; Fantin, Alberto; Guarneri, Valentina; Pasello, Giulia (Frontiers in Oncology, 2023)
Introduction. REarranged during Transfection (RET) gene rearrangements occur in 1-2% of Non-Small Cell Lung Cancer (NSCLC). Thanks to the results of the study LIBRETTO-001 has been approved as first-line treatment for RET fusion positive advanced (a)NSCLC patients. Selpercatinib demonstrated to be well tolerated. Despite this, gastro-intestinal Adverse Events (AEs) are frequently reported and no clinicalradiological and endoscopic features, their impact in terms of treatment discontinuations, interruptions and dose reductions have been described so far.Case Report. A 37-years old never-smoker woman was treated in our institution with selpercatinib for a RETfusion positive NSCLC. After nine months of treatment the patient referred abdominal pain of Grade (G) 2, associated with nausea G2, bilious vomiting G3 and weight loss G1. At computed tomography (CT) scan the presence of important bowel wall thickening, free ascitic fluid, mesenteric congestion and stranding was detected. The patient underwent an anterograde enteroscopy extended to jejunum with detection of lymphocytic duodenitis with sub-mucosal edema. Selpercatinib treatment was temporary interrupted with complete resolution of the symptoms and then re-administered with dose reduction, without relapsed of the gastro-intestinal toxicity after 120 days.To our knowledge this is the first case report of a NSCLC patient treated with selpercatinib outside a clinical study who developed severe gastro-intestinal toxicity characterized by small bowel edema and lymphocytic duodenitis leading to treatment interruption and dose reduction. The gastro-intestinal AE has been described by a radiological, endoscopic, and histo-pathological point of view. Further investigations are needed to better identify pathological mechanisms of gastro-intestinal toxicity for an appropriate AEs management.Eliminato: .